Alchevsky Family Within Kharkiv Theatre Space - Полякова, Юліана (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2017)
The article presents an analysis of the contribution to the life of the theaters in Kharkiv, made by the Alchevsky family at the turn of the 20th century. Special attention is paid for the works by Kh. Alchevska, who aptly used the impact of the plays and the theater performances to enhance her teaching at school. A part of the article deals with the family’s connections in the world of theaters as those connections stimulated the progress of Ivan Alchevsky as an outstanding singer. The other prominent figure was Hryhory Alchevsky, a musician and a composer. His theater reviews in the press are analyzed by the author. The research allows to the conclusion that Alchevsky family managed to influence the rise of culture between both theater-goers and actors in Kharkiv of their epoch.